Characteristics and longitudinal progression of chronic obstructive pulmonary disease in GOLD B patients. Issue 1 (December 2017) - Lawrence, Philip; Kolsum, Umme; Gupta, Vandana; Donaldson, Gavin; Singh, Richa; Barker, Bethan; George, Leena; Webb, Adam; Brookes, Anthony; Brightling, Christopher; Wedzicha, Jadwiga; Singh, Dave
Abstract Background The characteristics and natural history of GOLD B COPD patients are not well described. The clinical characteristics and natural history of GOLD B patients over 1 year in a multicentre cohort of COPD patients in the COPDMAP study were assessed. We aimed to identify the subgroup of patients who progressed to GOLD D (unstable GOLD B patients) and identify characteristics associated with progression. Methods Three hundred seventy COPD patients were assessed at baseline and 12 months thereafter. Demographics, lung function, health status, 6 min walk tests and levels of systemic inflammation were assessed. Students t tests and Mann Whitney-U tests were used. Results One hundred seven (28.9%) of patients were categorised as GOLD B at baseline. These GOLD B patients had similar FEV1 to GOLD A patients (66% predicted). More GOLD B patients were current smokers (p  = 0.031), had chronic bronchitis (p  = 0.0003) and cardiovascular comorbidities (p  = 0.019) compared to GOLD A. At 12 months, 25.3% of GOLD B patients progressed to GOLD D. These patients who progressed (unstable patients) had worse health status and symptoms (SGRQ-C Total, 50.0 v 41.1, p  = 0.019 and CAT, 21.0 v 14.0, p  = 0.006) and lower FEV1 (60% v 69%p  = 0.014) at baseline compared to stable patients who remained in GOLD B. Conclusions Unstable GOLD B patients who progressed to GOLD D had a higher level of symptoms at baseline. A high symptom burden may predict an increased likelihood of disease progression in GOLD B patients.